Geology of the Macao Special Administrative Region (China). Issue 2 (1st December 2021) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João
ABSTRACT: A 1:12, 000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies. GRAPHICAL ABSTRACT: UF0001